Liquid-liquid equilibria of systems containing perfluoromethylcyclohexane - Bernardo-Gil, M. G. (1990)
Liquidliquid equilibria for the quaternary system perfluoromethylcyclohexane (PFMCH)1-heptenen-heptanen-hexane at 288.15 K and for the ternary systems PFMCH1-heptenen-heptane, PFMCH1-heptenen-hexane and PFMCHn-heptanen-hexane at 279.15 K and 288.15 K are reported. The experimental results are compared with predicted values calculated using the NRTL and the UNIQUAC models.